2019
DOI: 10.1002/pssa.201900316
|View full text |Cite
|
Sign up to set email alerts
|

Etch Pit Density Reduction in POCl3 and Atmospheric Pressure Chemical Vapor Deposition‐Gettered mc‐Si

Abstract: Herein, the effects of gettering, temperature, dopant concentration, and metal contamination on the etch pit density (EPD) of an mc‐Si material are studied. It is demonstrated that there is a reduction of EPD after gettering that is independent for varying etchants, thereby confirming the physical nature of this effect. The EPD analysis of wafers that are gettered on one wafer side, results in different EPD values for the two wafer sides. This finding constrains the possibilities for mechanisms of EPD reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this paper an algorithm is presented that allows to combine the precision of optical microscope images sufficient for counting individual etch pits with analysis of large wafer areas of several cm 2 . This technique has been successfully applied for detection and investigation of changes in etch pit density due to gettering steps [5]. In the following it is explained how wafers are prepared, defect etching is executed and how optical microscope data is reduced to EPD values.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper an algorithm is presented that allows to combine the precision of optical microscope images sufficient for counting individual etch pits with analysis of large wafer areas of several cm 2 . This technique has been successfully applied for detection and investigation of changes in etch pit density due to gettering steps [5]. In the following it is explained how wafers are prepared, defect etching is executed and how optical microscope data is reduced to EPD values.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that mobile dislocations can be removed from the material via several mechanisms, including out‐diffusion to surfaces or pairwise annihilation. [ 35,36 ] We can conclude that it is the b‐Si layer, due to the large surface area, during oxidation ensures the absorption of the dislocations. The observed decrease in EPD with an increase in the oxidation temperature is associated with an increase in the thermal activation of the processes of impurities segregation and dislocation diffusion.…”
Section: Resultsmentioning
confidence: 97%